Diary of a Wimpy Kid: Wrecking Ball - Book 14 - Kinney, Jeff (New York : Amulet Books, 2019)
"An unexpected inheritance gives Greg Heffley's family a chance to make big changes to their house. But they soon find that home improvement isn't all it's cracked up to be"--|cProvided by publisher.
Keywords: Heffley, Greg -- Juvenile fiction; Heffley, Greg -- Fiction; Diaries -- Juvenile fiction; Inheritance and succession -- Juvenile fiction; Dwellings -- Juvenile fiction -- Maintenance and repair; Families -- Juvenile fiction; Humorous Stories; Diaries -- Fiction; Inheritance and succession -- Fiction; Dwellings -- Fiction -- Maintenance and repair; Family life -- Fiction; Humorous Stories; JUVENILE FICTION / Humorous Stories